Desenvolvimento de um bioprocesso para a sacarificação de grãos de cevada - Lopes, Dagma Maria (2013)
The aim of this study was to develop a process for obtaining a new malt with high concentration of fermentable sugars. It was aimed to reduce the mashing time of comparing to conventional breweries processes. The proposed method was to develop a solid state fermentation (SSF) by Aspergillus niger and Aspergillus oryzae 2220 using barley grains. The capacity of production of enzymes and biomass was tested for 8 days under constant temperature at 28 ° C in SSF Bioreactor trays containing untreated barley inoculated with micro-organisms listed above. The most important production of amylolytic enzymes (α and β amylases) for Aspergillus oryzae 2220 was reach 8th day after inoculation (34.162 U / g db) and Aspergillus niger W2, on the 4th day (11,721 U / g db). The maximum concentration for reducing sugars for Aspergillus oryzae 2220 was obtained the 8th day (5.68 g / L) and Aspergillus niger W2 (5,212 g / L) also on the 8th day. The higher biomass production after the 8th day for Aspergillus oryzae 2220 was 99.884 mg biomass / g fermented and Aspergillus niger W2, 822.72 mg biomass / g fermented. Studies were conducted to study the temperature for saccharification fermentation by Aspergillus oryzae, because there is few reference data in the literature, obtaining the best result temperature at 40 ° C with a concentration of 26.82 g / L. Verification was carried out by 5.8 ° Brix, ° Brix under pH 5.5. Comparing the malt mashing between alternative and standard pilsen malt, it was obtained the following results: standard pilsen malt (reducing sugars, 112.29 g / L, 14.0 ° Brix and pH 5.3) and alternative malt (reducing sugars 8.68 g / L, 5.4 ° Brix and pH 5.7). We conclude that the production of sugars by the alternative method was insufficient for obtaining malt mash compared to usual.